Neurogenic bowel dysfunction: Clinical management recommendations of the Neurologic Incontinence Committee of the Fifth International Consultation on Incontinence 2013. Issue 1 (22nd June 2017) - Cotterill, Nikki; Madersbacher, Helmut; Wyndaele, Jean J.; Apostolidis, Apostolos; Drake, Marcus J.; Gajewski, Jerzy; Heesakkers, John; Panicker, Jalesh; Radziszewski, Piotr; Sakakibara, Ryuji; Sievert, Karl‐Dietrich; Hamid, Rizwan; et al.
Abstract : Background: Evidence‐based guidelines for the management of neurological disease and lower bowel dysfunction have been produced by the International Consultations on Incontinence (ICI). These are comprehensive guidelines, and were developed to have world‐wide relevance. Aims: To update clinical management of neurogenic bowel dysfunction from the recommendations of the 4th ICI, 2009. Materials and Methods: A series of evidence reviews and updates were performed by members of the working group. The resulting guidelines were presented at the 2012 meeting of the European Association of Urology for consultation, and modifications applied to deliver evidence based conclusions and recommendations for the scientific report of the 5th edition of the ICI in 2013. Results: The current review is a synthesis of the conclusions and recommendations, including the algorithms for initial and specialized management of neurogenic bowel dysfunction. The pathophysiology is described in terms of spinal cord injury, multiple sclerosis, and Parkinson's disease. Assessment requires detailed history and clinical assessment, general investigations, and specialized testing, if required. Treatment primarily focuses on optimizing stool consistency and regulating bowel evacuation to improve quality of life. Symptom management covers conservative and interventional measures to promote good habits and assist stool evacuation, along with prevention of incontinence. Education is essential to achieving optimal bowel management. Discussion: The review offers a pragmatic approach to management in the context of complex pathophysiology and varied evidence base.